The impact of inflation risk on forward trading and production - Udo Broll; Kit Pong Wong (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2014)
This note examines the behavior of a competitive firm that faces joint price and inflation risk. Given that the price risk is negatively correlated with the inflation risk in the sense of expectation dependence, the firm optimally opts for an overhedge if the firm's coefficient of relative risk aversion is everywhere no greater than unity. Furthermore, banning the firm from forward trading may induce the firm to produce more or less, depending on whether the price risk premium is positive or negative, respectively. While the price risk premium is unambiguously negative in the absence of the inflation risk, it is not the case when the inflation risk prevails. In contrast to the conventional wisdom, forward hedging needs not always promote production should firms take in inflation seriously.
Keywords: D21; D24; D81; 330; Forward markets; Expectation dependence; Inflation risk; Production